Intervención fisioterapéutica en paciente de sexo masculino de 49 años de edad con dolor en la movilidad del hombro derecho tras cirugía del tendón supraespinoso. - Caicedo Fernández, Nayeli Dayana (2023)
The present research work focuses on the physiotherapeutic treatment in the patient Mario Guerrero Gómez, 49 years old, who suffers from pain after a surgical intervention performed on the supraspinatus tendon. This procedure can be performed with a large incision or with an arthroscopy of the shoulder. which uses smaller incisions. The pain appears on the anterior surface of the shoulder only when moving. The general objective is to develop an optimal therapeutic plan for the recovery of the patient treated at the IESS hospital after a surgical procedure on the supraspinatus tendon. Therefore, it was decided to create an ideal physiotherapy treatment plan based on the latest scientific evidence, with the appropriate times and procedures for recovery from these conditions. By combining several physical therapy options related to this pathology, the results will show an improvement in the function and symptoms of this patient.